VIOLATION OF CARBOHYDRATE METABOLISM IN CUSHING'S SYNDROME - Yulduzkhan Kholmatova; G.J. Narimova; H.Q. Nasirova (Scholar Express Journals, 2021)
Analysis of the rhythm and level of incretin secretion in patients with acromegaly and Itsenko-Cushing's disease (ICD), depending on the identified disorders of carbohydrate metabolism
Keywords: Acromegaly; Disease; Disorders Of Carbohydrate Metabolism; Incretins